Pengolahan Air Limbah Proses Utama Menggunakan Wastewater Treatment Plant pada PT. Indonesia Power Grati POMU - Theresia A. E. D. Willy; J. Mukono (Media Gizi Kesmas, 2023)
Background: Population growth, economy, and technology supported by a high level of productivity, more and more waste is produced every day, both solid, liquid, gas and B3 waste, the best way to overcome environmental damage due to waste is by managing waste before being released or discharged into the environment. Waste management is adjusted to environmental quality standards that have been regulated in applicable laws so as not to cause environmental damage, waste treatment is carried out at PT. Indonesia Power Grati POMU with a generation unit in the form of PLTGU (Gas and Steam Power Plant), one of which is the Wastewater Treatment Plant (WWTP) method. Objectives: determine the process of wastewater treatment using the Wastewater Treatment Plant (WWTP) method carried out by PT. Indonesia Power Gratai POMU. Methods: This research was a descriptive study where describes the main process wastewater treatment with the wastewater treatment plant (WWTP) method at PT. Indonesia Power Grati Power Generation and Operation and Maintenance Service Unit (POMU), the study was conducted a direct observation approach at place of WWTP and literacy related to applicable laws and regulations Results: The wastewater treatment process at PT. Indonesia Power Grati POMU has 10 stages, starting from the storage pond to being discharged into the sea. Conclusions: PT. Indonesia Power Grati POMU uses the wastewater treatment method plant (WWTP) for main process wastewater treatment There are 10 stages in the WWTP treatment process, wastewater treatment using this process has been well marked by the results of WWTP processing in 2021-January 2022 with results below quality standards so that they are suitable for disposal into the sea.